Posttranslational Acetylation of the Human Immunodeficiency Virus Type 1 Integrase Carboxyl-Terminal Domain Is Dispensable for Viral Replication - Topper, Michael (American Society for Microbiology, 2007)
A recent report sought to demonstrate that acetylation of specific lysines within integrase (IN) by the histone acetyltransferase (HAT) p300 regulates human immunodeficiency virus type 1 (HIV-1) integration and is essential for viral replication (A. Cereseto, L. Manganaro, M. I. Gutierrez, M. Terreni, A. Fittipaldi, M. Lusic, A. Marcello, and M. Giacca, EMBO J. 24:3070-3081, 2005). We can corroborate the efficient and specific acetylation of the IN carboxyl-terminal domain (CTD) (amino acids 212 to 288) by p300 using purified recombinant components. Although arginine substitution mutagenesis of the isolated CTD confirms that the majority of p300 acetylation occurs at lysine residues 264, 266, and 273, the pattern of acetylation is not uniform and a hierarchy of reactivity can be established. Several combinatorial mutations of the CTD lysines modified by p300 in vitro were reconstructed into an otherwise infectious proviral plasmid clone and examined for viral growth and frequency of productive chromosomal integration. In contrast to the findings of Cereseto and coworkers, who used epitope-tagged viruses for their experiments, we find that an untagged mutant virus, IN K(264/266/273)R, is fully replication competent. This discrepancy may be explained by the use of an acidic epitope tag placed at the extreme carboxyl terminus of integrase, near the target site for acetylation. Although the tagged, wild-type virus is viable, the combination of this epitope tag with the RRR substitution mutation results in a replication-defective phenotype. Although IN belongs to the very small set of nonhistone proteins modified by HAT-mediated activity, an obligate role for acetylation at the reactive CTD lysines in HIV-1 IN cannot be confirmed.